High-performance composite material and preparation method thereof

By optimizing the preparation process and raw material matching, especially by using fillers in combination with hydroxyl-terminated polydimethylsiloxane, the problem of insufficient wear resistance and toughness of nylon/POK composite materials has been solved, realizing the preparation of high-performance composite materials and expanding their application fields.

CN120818233AActive Publication Date: 2025-10-21POLYSTAR ENG PLASTICS (SHANGHAI) CO LTD +1
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
CN202511302567.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2025-10-21
Estimated Expiration
2045-09-12

AI Technical Summary

Technical Problem

Existing nylon/POK composite materials have deficiencies in wear resistance and toughness, which limits their application in complex scenarios.

Method used

High-performance composite materials are prepared by using raw materials such as nylon resin, POK resin, hydroxyl-terminated polydimethylsiloxane, antioxidants, flame retardants, lubricants, fillers, and glass fibers, through specific preparation processes including stirring, heating, and calcination. The combination of fillers and hydroxyl-terminated polydimethylsiloxane enhances the wear resistance and toughness of the materials.

Benefits of technology

This improved the wear resistance and toughness of the composite material, expanding its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818233A_ABST
    Figure CN120818233A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a high-performance composite material and a preparation method thereof. The high-performance composite material is prepared from the following raw materials in parts by weight: 80 to 90 parts of nylon resin, 20 to 30 parts of POK resin, 5 to 10 parts of hydroxyl-terminated polydimethylsiloxane, 0.1 to 0.3 part of antioxidant, 3 to 8 parts of flame retardant, 0.05 to 1 part of lubricant, 15 to 21 parts of filler and 20 to 30 parts of glass fiber. And the filler and the hydroxyl-terminated polydimethylsiloxane are matched for use, so that the wear resistance and toughness of the composite material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and in particular relates to a high-performance composite material and a preparation method thereof. Background Art

[0002] Nylon 66, scientifically known as polyamide (PA66), is a generic term for thermoplastic resins containing repeating amide groups in their main molecular chain. It is widely used in automotive parts, mechanical components, electronic and electrical products, engineering accessories, cable ties, and other products. Its excellent mechanical properties make it a crucial component in modern industry. However, its poor wear resistance significantly limits its application.

[0003] POK (polyketone) is a new green polymer material formed by the polymerization of carbon monoxide, ethylene, and propylene. It is a high-performance engineering plastic with a dense crystalline structure formed by a carbon-hydrogen backbone. Due to its advantages such as impact resistance, wear resistance, and temperature resistance, it is widely used in automotive parts, electronic and electrical components, medical devices, and food packaging. However, it also has some inherent drawbacks, such as low strength and modulus.

[0004] With technological advancements and increasing demands for specialized product performance, a variety of nylon / POK composite materials have emerged on the market. However, existing materials still suffer from technical issues such as insufficient wear resistance and toughness, which in turn limits their application in complex applications. Therefore, developing nylon / POK composite materials with high wear resistance and toughness can effectively expand the application areas of nylon / POK materials and has significant practical value. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the first object of the present invention is to provide a high-performance composite material with high wear resistance and high toughness.

[0006] The second object of the present invention is to provide a method for preparing a high-performance composite material with a simple preparation process.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: A high-performance composite material comprises the following raw materials in parts by weight: 80-90 parts of nylon resin, 20-30 parts of POK resin, 5-10 parts of hydroxyl-terminated polydimethylsiloxane, 0.1-0.3 parts of antioxidant, 3-8 parts of flame retardant, 0.05-1 parts of lubricant, 15-21 parts of filler and 20-30 parts of glass fiber.

[0008] Furthermore, the nylon resin is PA66.

[0009] Furthermore, the preparation process of the filler is as follows: (1) adding sodium carbonate to a manganese nitrate solution and stirring the solution to react; after the reaction is completed, aging the solution at room temperature to obtain a mixed solution; (2) adding the pretreated diatomaceous earth to water, and then adding the mixed solution of step (1) to carry out heating reaction. After the reaction is completed, aging is carried out at room temperature, and the diatomaceous earth composite is obtained by filtering, washing, and drying; (3) Adding the diatomaceous earth composite of step (2) into toluene containing a silane coupling agent and stirring the mixture, filtering, washing, and drying the mixture after stirring to obtain the filler.

[0010] Furthermore, the dosage ratio of the sodium carbonate and manganese nitrate solution in step (1) is 1 g: (50-100) mL; the concentration of the manganese nitrate solution is 0.2-0.5 mol / L; the stirring reaction temperature is 60-70° C., the stirring reaction time is 1-2 h; and the aging time is 46-50 h.

[0011] Furthermore, in step (2), the mass ratio of the pretreated diatomaceous earth to the mixed solution is 1:(10-20); the temperature of the heating reaction is 60-70°C, the heating reaction time is 4-6 hours; and the aging time is 22-26 hours.

[0012] Furthermore, the preparation method of pretreated diatomaceous earth is as follows: diatomaceous earth is added to nitric acid with a concentration of 3-5 mol / L and stirred for reaction; after the reaction is completed, the product is washed to neutrality, and then calcined and sieved to obtain the product.

[0013] Furthermore, the stirring reaction temperature is 60-70° C., and the stirring reaction time is 6-9 hours; the calcination temperature is 450-550° C., and the calcination time is 0.5-1.5 hours; and the sieving mesh size is 300-500 mesh.

[0014] Furthermore, in step (3), the mass ratio of the diatomaceous earth composite to the silane coupling agent is 1:(0.05-0.1); the silane coupling agent is isocyanatepropyltriethoxysilane; the stirring temperature is 60-70° C., and the stirring time is 1-3 h.

[0015] Furthermore, the antioxidant is antioxidant 168 or antioxidant 1010, the flame retardant is melamine cyanurate, and the lubricant is pentaerythritol stearate or polyethylene wax.

[0016] The method for preparing the high-performance composite material comprises the following steps: The raw materials are weighed and pre-mixed according to the weight ratio, and then melted, extruded, cooled, granulated and dried to obtain the high-performance composite material.

[0017] Furthermore, the pre-mixing time is 3-5 minutes; and the temperature range of each temperature zone of the melt extrusion is 210-235°C.

[0018] The beneficial technical effects of the present invention are: The filler obtained by the present invention, when used in combination with hydroxyl-terminated polydimethylsiloxane, can improve the wear resistance and toughness of the composite material. This is likely due to the increased internal pore structure of the pretreated diatomaceous earth, followed by pillar modification with a manganese nitrate solution, which improves the material's stability and wear resistance. Surface modification with a silane coupling agent improves the filler's compatibility with the substrate and forms ester bonds with the hydroxyl groups of the hydroxyl-terminated polydimethylsiloxane, further enhancing the material's toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the SEM image of the filler obtained in Example 1. DETAILED DESCRIPTION

[0020] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it is not intended that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, without departing from the inventive concept, several simple deductions or replacements can also be made, all of which should be considered to belong to the scope of protection of the present invention. The specific conditions not indicated in the examples are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0021] The nylon resin involved in the examples and comparative examples of the present invention is PA66.

[0022] Example 1 This embodiment provides a high-performance composite material, which is composed of the following raw materials in parts by weight: 85 parts of nylon resin, 22 parts of POK resin, 7 parts of hydroxyl-terminated polydimethylsiloxane, 0.2 parts of antioxidant 168, 5 parts of melamine cyanurate, 0.08 parts of pentaerythritol stearate, 19 parts of filler, and 22 parts of glass fiber.

[0023] The preparation method of the above filler is as follows: (1) Sodium carbonate was added to a 0.3 mol / L manganese nitrate solution at a ratio of 1 g to 80 mL, and the mixture was stirred at 65°C for 1.5 h. After the reaction was complete, the mixture was aged at room temperature for 48 h to obtain a mixed solution. (2) adding diatomaceous earth to nitric acid with a concentration of 4 mol / L, stirring and reacting at 65°C for 7 h, washing the product to neutrality after the reaction is completed, calcining at 500°C for 1 h, and passing through a 400-mesh sieve to obtain pretreated diatomaceous earth; adding the pretreated diatomaceous earth to water according to the mass ratio of pretreated diatomaceous earth to mixed solution of 1:15, and then dropwise adding the mixed solution of step (1), heating and reacting at 65°C for 5 h, aging at room temperature for 24 h after the reaction is completed, filtering, washing, and drying to obtain a diatomaceous earth composite; (3) The diatomaceous earth composite of step (2) was added to toluene containing isocyanatepropyl triethoxysilane in a mass ratio of 1:0.07, and stirred at 65°C for 2 hours. After stirring, the mixture was filtered, washed, and dried to obtain the filler. The SEM image of the filler is shown in FIG. Figure 1 .

[0024] This embodiment also provides a method for preparing the above-mentioned high-performance composite material. The specific preparation method is as follows: According to the weight ratio, the raw materials were weighed and pre-mixed for 4 minutes, and then put into a twin-screw extruder for melt blending and extrusion granulation to obtain the high-performance composite material; the screw speed of the twin-screw extruder was 300 rpm, the temperatures of each temperature zone of the extruder were 220°C in zone 1, 235°C in zone 2, 235°C in zone 3, 235°C in zone 4, 210°C in zone 5, 210°C in zone 6, 210°C in zone 7, 210°C in zone 8, 210°C in zone 9, and 230°C in the die head, and the vacuum degree was -0.1 MPa.

[0025] Example 2 This embodiment provides a high-performance composite material, which is composed of the following raw materials in parts by weight: 90 parts of nylon resin, 30 parts of POK resin, 10 parts of hydroxyl-terminated polydimethylsiloxane, 0.3 parts of antioxidant 1010, 8 parts of melamine cyanurate, 1 part of polyethylene wax, 21 parts of filler, and 30 parts of glass fiber.

[0026] The preparation method of the above filler is as follows: (1) Sodium carbonate was added to a 0.5 mol / L manganese nitrate solution at a ratio of 1 g to 100 mL, and the mixture was stirred at 70°C for 1 h. After the reaction was complete, the mixture was aged at room temperature for 50 h to obtain a mixed solution. (2) adding diatomaceous earth to nitric acid with a concentration of 5 mol / L, stirring and reacting at 70°C for 6 h, washing the product to neutrality after the reaction is completed, calcining at 550°C for 0.5 h, and passing through a 500-mesh sieve to obtain pretreated diatomaceous earth; adding the pretreated diatomaceous earth to water according to the mass ratio of pretreated diatomaceous earth to mixed solution of 1:20, and then dropwise adding the mixed solution of step (1), heating and reacting at 70°C for 4 h, aging at room temperature for 26 h after the reaction is completed, filtering, washing, and drying to obtain a diatomaceous earth composite; (3) The diatomaceous earth composite of step (2) was added to toluene containing isocyanatepropyltriethoxysilane in a mass ratio of 1:0.1 between the diatomaceous earth composite and isocyanatepropyltriethoxysilane, and the mixture was stirred at 70° C. for 1 h. After stirring, the mixture was filtered, washed, and dried to obtain the filler.

[0027] This embodiment also provides a method for preparing the above-mentioned high-performance composite material. The specific preparation method is as follows: According to the weight ratio, the raw materials were weighed and pre-mixed for 5 minutes, and then put into a twin-screw extruder for melt blending and extrusion granulation to obtain the high-performance composite material; the screw speed of the twin-screw extruder was 300 rpm, the temperatures of each temperature zone of the extruder were 220°C in zone 1, 235°C in zone 2, 235°C in zone 3, 235°C in zone 4, 210°C in zone 5, 210°C in zone 6, 210°C in zone 7, 210°C in zone 8, 210°C in zone 9, and 230°C in the die head, and the vacuum degree was -0.1 MPa.

[0028] Example 3 This embodiment provides a high-performance composite material, which is composed of the following raw materials in parts by weight: 80 parts of nylon resin, 20 parts of POK resin, 5 parts of hydroxyl-terminated polydimethylsiloxane, 0.1 parts of antioxidant 168, 3 parts of melamine cyanurate, 0.05 parts of polyethylene wax, 15 parts of filler, and 20 parts of glass fiber.

[0029] The preparation method of the above filler is as follows: (1) Sodium carbonate was added to a 0.2 mol / L manganese nitrate solution at a ratio of 1 g to 50 mL, and the mixture was stirred at 60°C for 2 h. After the reaction was complete, the mixture was aged at room temperature for 46 h to obtain a mixed solution. (2) adding diatomaceous earth to nitric acid with a concentration of 3 mol / L, stirring and reacting at 60°C for 9 h, washing the product to neutrality after the reaction, calcining at 450°C for 1.5 h, and passing through a 300-mesh sieve to obtain pretreated diatomaceous earth; adding the pretreated diatomaceous earth to water according to the mass ratio of pretreated diatomaceous earth to mixed solution of 1:10, and then dropwise adding the mixed solution of step (1), heating and reacting at 60°C for 6 h, aging at room temperature for 22 h after the reaction is completed, filtering, washing, and drying to obtain a diatomaceous earth composite; (3) The diatomaceous earth composite of step (2) was added to toluene containing isocyanatepropyltriethoxysilane in a mass ratio of 1:0.05, and the mixture was stirred at 60° C. for 3 h. After stirring, the mixture was filtered, washed, and dried to obtain the filler.

[0030] This embodiment also provides a method for preparing the above-mentioned high-performance composite material. The specific preparation method is as follows: According to the weight ratio, the raw materials were weighed and pre-mixed for 3 minutes, and then put into a twin-screw extruder for melt blending and extrusion granulation to obtain the high-performance composite material; the screw speed of the twin-screw extruder was 300 rpm, the temperatures of each temperature zone of the extruder were 220°C in zone 1, 235°C in zone 2, 235°C in zone 3, 235°C in zone 4, 210°C in zone 5, 210°C in zone 6, 210°C in zone 7, 210°C in zone 8, 210°C in zone 9, and 230°C in the die head, and the vacuum degree was -0.1 MPa.

[0031] Comparative Example 1 The difference between this comparative example and Example 1 is that the filler is replaced with diatomaceous earth, and the rest is the same as Example 1.

[0032] Comparative Example 2 The difference between this comparative example and Example 1 is that the preparation process of the filler is different, and the rest is the same as Example 1.

[0033] The preparation process of this comparative example filler is as follows: (1) Add diatomaceous earth to nitric acid with a concentration of 4 mol / L, stir and react at 65°C for 7 h. After the reaction is completed, wash the product to neutrality, calcine at 500°C for 1 h, and pass through a 400 mesh sieve to obtain pretreated diatomaceous earth; (2) The pretreated diatomaceous earth of step (1) was added to toluene containing isocyanatepropyltriethoxysilane in a mass ratio of 1:0.07, and the mixture was stirred at 65° C. for 2 h. After stirring, the mixture was filtered, washed, and dried to obtain the product.

[0034] Comparative Example 3 The difference between this comparative example and Example 1 is that the hydroxyl-terminated polydimethylsiloxane is replaced by polydimethylsiloxane, and the rest is the same as Example 1.

[0035] Comparative Example 4 The difference between this comparative example and Example 1 is that the hydroxyl-terminated polydimethylsiloxane is omitted, and the rest is the same as Example 1.

[0036] The properties of the materials obtained in Examples 1-3 and Comparative Examples 1-4 of the present invention are described below.

[0037] Mechanical properties test: The mechanical properties of the composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested according to the American Society for Testing and Materials (ASTM) standards, where the notched impact strength was measured according to ASTM D256, the tensile strength was measured according to ASTM D638, and the flexural modulus was measured according to ASTM D790. Specific test results are shown in Table 1.

[0038] Wear resistance test: The friction coefficients of the composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested according to GB / T 3960-2016. The results are shown in Table 1.

[0039] Table 1 From Table 1, it can be seen that the composite materials obtained in Examples 1-3 have excellent toughness and wear resistance.

[0040] Compared with Example 1, Comparative Example 1 replaces the filler with diatomaceous earth, Comparative Example 2 adjusts the preparation method of the filler, Comparative Example 3 replaces hydroxyl-terminated polydimethylsiloxane with polydimethylsiloxane, and Comparative Example 4 omits hydroxyl-terminated polydimethylsiloxane. The wear resistance and toughness of the composite material obtained are reduced. The above results show that the filler obtained by the present invention is used in combination with hydroxyl-terminated polydimethylsiloxane to improve the wear resistance and toughness of the composite material. This may be because the internal pore structure of the pre-treated diatomaceous earth is increased, and then the pillar modification with manganese nitrate solution is performed, which can improve the stability and wear resistance of the material. The surface modification of the diatomaceous earth with a silane coupling agent can improve the compatibility of the filler in the substrate on the one hand, and on the other hand, the silane coupling agent and the hydroxyl group of the hydroxyl-terminated polydimethylsiloxane can form an ester bond, thereby improving the toughness of the material.

[0041] Finally, it should be noted that the above embodiments are intended only to illustrate the technical solutions of the present invention and are not intended to limit the same. The basic principles and main features of the present invention have been described above using specific implementation schemes. Modifications or substitutions may be made based on the present invention, but such modifications or substitutions do not detract from the essence of the corresponding technical solutions from the scope of protection claimed by the present invention.

Claims

1. A high-performance composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-90 parts of nylon resin, 20-30 parts of POK resin, 5-10 parts of hydroxyl-terminated polydimethylsiloxane, 0.1-0.3 parts of antioxidant, 3-8 parts of flame retardant, 0.05-1 parts of lubricant, 15-21 parts of filler and 20-30 parts of glass fiber.

2. The high-performance composite material according to claim 1, characterized in that: The preparation process of the filler is as follows: (1) adding sodium carbonate to a manganese nitrate solution and stirring the solution to react; after the reaction is completed, aging the solution at room temperature to obtain a mixed solution; (2) adding the pretreated diatomaceous earth to water, and then adding the mixed solution of step (1) to carry out heating reaction. After the reaction is completed, aging is carried out at room temperature, and the diatomaceous earth composite is obtained by filtering, washing, and drying; (3) Adding the diatomaceous earth composite of step (2) into toluene containing a silane coupling agent and stirring, filtering, washing, and drying after stirring to obtain the filler.

3. The high performance composite material according to claim 2, characterized in that: The dosage ratio of the sodium carbonate and manganese nitrate solution in step (1) is 1 g: (50-100) mL; the concentration of the manganese nitrate solution is 0.2-0.5 mol / L; the stirring reaction temperature is 60-70° C., the stirring reaction time is 1-2 h; and the aging time is 46-50 h.

4. The high performance composite material according to claim 2, characterized in that: The mass ratio of the pretreated diatomaceous earth to the mixed solution in step (2) is 1:(10-20); the temperature of the heating reaction is 60-70°C, the heating reaction time is 4-6 hours; and the aging time is 22-26 hours.

5. The high performance composite material according to claim 4, characterized in that: The preparation method of pretreated diatomite is as follows: adding diatomite to nitric acid with a concentration of 3-5 mol / L for stirring reaction; after the reaction is completed, washing the product to neutrality, calcining and sieving to obtain the product.

6. The high-performance composite material according to claim 5, characterized in that: The stirring reaction temperature is 60-70° C., and the stirring reaction time is 6-9 hours; the calcination temperature is 450-550° C., and the calcination time is 0.5-1.5 hours; and the sieving mesh size is 300-500 mesh.

7. The high performance composite material according to claim 2, characterized in that: The mass ratio of the diatomaceous earth composite to the silane coupling agent in step (3) is 1:(0.05-0.1); the silane coupling agent is isocyanatepropyltriethoxysilane; the stirring temperature is 60-70° C., and the stirring time is 1-3 h.

8. The high performance composite material according to claim 1, characterized in that: The antioxidant is antioxidant 168 or antioxidant 1010, the flame retardant is melamine cyanurate, and the lubricant is pentaerythritol stearate or polyethylene wax.

9. The method for preparing a high-performance composite material according to any one of claims 1 to 8, characterized in that: The steps include: The raw materials are weighed and pre-mixed according to the weight ratio, and then melt-extruded, cooled, granulated and dried to obtain the high-performance composite material.

10. The method for preparing a high-performance composite material according to claim 9, characterized in that: The pre-mixing time is 3-5 minutes; the temperature range of each temperature zone of the melt extrusion is 210-235°C.

Citation Information

Patent Citations

  • Copolymerization nylon composition and preparation thereof

    CN101469126A

  • Thermoplastic composition based on polyamide, polyketone and novolac resin

    CN102844378A

  • Heat insulation phase change coating and preparation method thereof

    CN103642364A

  • High-gloss scratch-resistant polyamide composition and preparation method thereof

    CN106977911A

  • Resin composition and molded article thereof

    CN107531995A